Special Schooling for Indigenous Students: a New Form of Racial Discrimination? - de Plevitz, Loretta (The Australian Journal of Indigenous Education, 2006)
Abstract Recent reports on Indigenous education have revealed that high proportions of students have been placed in special classes for intellectual disability or behaviour disorders. This is not an isolated phenomenon. Indigenous students in Canada and Romani children in Europe are also disproportionately represented in special schooling. This paper asks whether systemic racism, which fails to perceive cultural differences between the ethos of Australian educational systems and the experiences and abilities of Indigenous students, is the catalyst for placing many Indigenous students in special schooling, away from the mainstream. The paper applies an analysis based on anti-discrimination law to argue that while allocation on the basis of intellectual disability or behaviour disorders may not be deliberate racism, the criteria developed for the allocation may be measuring conformity to the dominant culture. If the policies underlying this segregation are unreasonable in the circumstances, they could constitute indirect racial discrimination against Indigenous students. Educational authorities could be liable in law, even though the effect on Indigenous students is unintentional and said to be for the students’ “own good”.